2007
DOI: 10.1038/sj.gene.6364451
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the 5q31 cytokine gene cluster are associated with psoriasis

Abstract: A multitiered genetic association study of 25 215 single-nucleotide polymorphisms (SNPs) in three case-control sample sets (1446 patients and 1432 controls) identified three IL13-linked SNPs (rs1800925, rs20541 and rs848) associated with psoriasis. Although the susceptibility effects at these SNPs were modest (joint allelic odds ratios (ORs): 0.76 to 0.78; P comb : 1.3EÀ03 to 2.50EÀ04), the association patterns were consistent across the sample sets, with the minor alleles being protective. Haplotype analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 29 publications
1
51
0
2
Order By: Relevance
“…The minor alleles of three SNPs within the IL13 region, rs205541*A, rs1800925*T and rs848*A were significantly associated with psoriatic disease (psoriasis and PsA) in Caucasians from Utah compared with healthy controls 16. A follow-up study by the same group that analysed 106 SNPs within the same region concluded that rs1800925*C confers the highest risk for psoriatic disease 21.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The minor alleles of three SNPs within the IL13 region, rs205541*A, rs1800925*T and rs848*A were significantly associated with psoriatic disease (psoriasis and PsA) in Caucasians from Utah compared with healthy controls 16. A follow-up study by the same group that analysed 106 SNPs within the same region concluded that rs1800925*C confers the highest risk for psoriatic disease 21.…”
Section: Discussionmentioning
confidence: 98%
“…The minor alleles of three single nucleotide polymorphisms (SNPs) within the IL13 gene region, rs1800925 within the promoter region of the IL13 gene, rs20541, an IL13 exon 4 missense SNP, Q144R and rs848, located within the 3′ untranslated region of IL13 , were less frequent in Caucasian psoriasis patients from Utah16 compared with healthy controls. The Genetics Association Information Network genome-wide study also showed an association between two IL13 polymorphisms, rs20541 and rs848, and psoriasis, with the major allele being the risk allele 17.…”
mentioning
confidence: 99%
“…A number of recent studies investigating the genetic susceptibility to PsV identified association to SNPs on chromosome 5q31 10 11. This region is rich in immune-related genes and contains, among others, a cluster of four interleukin ( IL ) genes.…”
Section: Introductionmentioning
confidence: 99%
“…25,[28][29][30][31] In addition, Zhang et al 32 have recently reported a strong non-MHC psoriasis-association with haplotypes at IL15 in Han Chinese and we have published suggestive findings implicating IL13 and/or other variants in the 5q31 cytokine-rich region. 33 In this study, we focused on the IL23R region and extended our initial genetic analysis by fine mapping the association signal over 336 kb in our three case-control sample sets. Haplotype, association decay with linkage disequilibrium and conditional association analyses were performed to shed light on the psoriasis genetics in this region of chromosome 1p31.3.…”
Section: Introductionmentioning
confidence: 99%